Malic Enzymes of Sinorhizobium Meliloti: A Study of Metabolomics and Protein-Protein Interactions - Smallbone, Laura Anne (My University, 2006)
Malic enzymes catalyze the oxidative decarboxylation of malate to pyruvate with the simultaneous reduction of a nicotinamide cofactor. It was previously reported that the nitrogen-fixing bacterium, Sinorhizobium meliloti, has two malic enzymes, a diphosphopyridine-dependent malic enzyme (DME) and a triphosphopyridine-dependent malic enzyme (TME). The dme gene is essential for symbiotic nitrogen-fixation in alfalfa root nodules and this symbiotic requirement cannot be met through increased expression of tme. In order to determine if a metabolic difference exists between the dme and tme mutants which might explain the symbiotic phenotypes, we conducted an analysis of intracellular and extracellular polar metabolomes. Differences noted between the intracellular profiles of the dme and tme mutant strains hinted at osmotic stress or a disturbance in central carbon metabolism. Extracellular studies indicated that dme mutant cells excreted at least 10-fold greater concentrations of both malate and fumarate. When considered together, the metabolic data implies that the DME enzyme is primarily responsible for the conversion of malate to pyruvate to generate acetyl-CoA whereas the TME enzyme must serve a secondary function within the cell.
While the C-terminal 320 amino acid regions from both DME and TME are similar in sequence to phosphotransacetylase enzymes, enzyme assays with DME and TME proteins have failed to detect PTA activity. Here we report that the chimeric malic enzyme structure is conserved among various gram negative bacteria including Agrobacterium tumefaciens, Escherichia coli, Bradyrhizobium japonicum and Porphyromonas gingivalis. Moreover these chimeric proteins are also present in the archaebacteria. Halobacterium salinarum and Haloarcula marismortui. To further our understanding of the functions of DME and TME in S. meliloti, we have fused protein domains from DME to an affinity tag consisting of strepII and a calmodulin binding peptide. To identify proteins interacting with this fusion, we expressed these protein fusion constructs in S. meliloti, prepared extracts containing the soluble proteins and passed these through tandem affinity chromatography columns. All proteins that coeluted with the fusion proteins appeared to be interacting with antibodies specific for the DME protein and so may have been aggregates or break-down products of DME.
Keywords: malic enzymes, Sinorhizobium meliloti, metabolomics, protein-protein interactions, oxidative, bacterium, dme gene, tme mutant